2020
DOI: 10.3390/su12072987
|View full text |Cite
|
Sign up to set email alerts
|

Can Flow Alleviate Anxiety? The Roles of Academic Self-Efficacy and Self-Esteem in Building Psychological Sustainability and Resilience

Abstract: A growing number of studies suggest that flow experience is associated with life satisfaction, eudaimonic well-being, and the perceived strength of one’s social and place identity. However, little research has placed emphasis on flow and its relations with negative experiences such as anxiety. The current study investigated the relations between flow and anxiety by considering the roles of self-esteem and academic self-efficacy. The study sample included 590 Chinese university students, who were asked to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 61 publications
5
54
0
3
Order By: Relevance
“…As for the first hypothesis, results indicated self-efficacy has a significantly negative effect on test anxiety. This result is in accord with both previous kinds of research demonstrating the potentiality of self-efficacy to alleviate test anxiety[ 13 24 32 33 48 49 50 ] and control-value theory,[ 26 ] which discusses that test anxiety results from cognitive assessments including (low) self-efficacy beliefs. This theory posits that academic self-efficacy (which would be deemed to be a cognitive appraisal) can be an antecedent of test anxiety and other negative emotions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As for the first hypothesis, results indicated self-efficacy has a significantly negative effect on test anxiety. This result is in accord with both previous kinds of research demonstrating the potentiality of self-efficacy to alleviate test anxiety[ 13 24 32 33 48 49 50 ] and control-value theory,[ 26 ] which discusses that test anxiety results from cognitive assessments including (low) self-efficacy beliefs. This theory posits that academic self-efficacy (which would be deemed to be a cognitive appraisal) can be an antecedent of test anxiety and other negative emotions.…”
Section: Discussionsupporting
confidence: 90%
“…[ 25 31 ] This hypothetical notion was substantiated by research studies indicating students suffering from low self-efficacy beliefs undergo high test anxiety. [ 13 32 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies that analyze logistic regressions with similar variables in opposite ways affirm that self-efficacy is a predictor of well-being in age diversity [48,49], which is the reason why it is associated with a positive mental state [34] and, in turn, is a precursor to the development of a positive academic [10,12] and general self-concept [50]. On the other hand, self-efficacy increases self-esteem and reduces anxiety [51]. All these influences can trigger a feeling of happiness that allows the subject to go beyond their own perspective, allowing them to put themselves in the other's place.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of studies that examine the link between perceived academic self-efficacy and fantasy, it should be noted that the influence of future thoughts can condition the behavior in positive or negative, and this will depend on the character of those thoughts. It can be observed that self-efficacy can have a positive motivational influence [14,51,52] and, moreover, that motivation contributes towards this high efficacy for the healing of various diseases, possibly due to its placebo effect [53]. Therefore, with a motivational increase as a result of this academic performance, whether with a higher or lower realistic character, this perceived academic self-efficacy and self-confidence will increase [13,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation